PERBANDINGAN UJI AKTIVITAS ANTIOKSIDAN INFUSA DAN DEKOKTA BUNGA TELANG (Clitoria ternatea L.) DENGAN METODE DPPH - Ni Luh Gde Mona Monika; I Made Wahyu Yogatama; Nyoman Rudi Kusuma; Ni Putu Ria Artini (Journal Pharmactive, 2025)
Free radicals are highly reactive molecules that can cause cellular damage and contribute to the development of various degenerative diseases. Butterfly pea flower (Clitoria ternatea L.) is a traditional medicinal plant rich in antioxidant compounds such as flavonoids, anthocyanins, and phenolics. This study aimed to evaluate the antioxidant activity of infusion and decoction preparations of butterfly pea flowers using the DPPH method. The research was conducted through laboratory experiments by measuring the IC?? value using UV-Vis spectrophotometry. The results showed that the infusion extract exhibited very strong antioxidant activity with an IC?? value of 31.25 ppm, while the decoction extract demonstrated moderate antioxidant activity with an IC?? value of 128.66 ppm. The positive control, Vitamin C, showed very strong antioxidant activity with an IC?? value of 14.04 ppm. Based on these findings, the infusion method is more effective at extracting antioxidant compounds than the decoction method. The infusion of butterfly pea flower has potential to be developed as a natural antioxidant source.